International Coffee Trade Network Analysis - Pancsira, János; Lengyel, Péter (International Journal of Engineering and Management Sciences, 2020)
Coffee is one of the most consumed beverages in the world. It is the second largest traded commodity after petroleum. It is crucial for the economy and politics of many developing countries, as its cultivation, processing, trade, transportation and distribution create jobs for millions of people. The analysis of network connections and structures became popular in the field of sociology, whereby the term Social Network Analysis (SNA) is derived. The method is well suited for the complex examination and modelling of composite social structures. The social network is defined as a finite set of social actors and the relationships between them. Modelling of complex networks now apply in countless locations, from social media through the pharmaceutical industry to economic and commercial processes. Our study examines changes in international coffee trade through a network analysis. Introducing the complex networks investigate by our, highlighting major changes in international coffee trade.